ASUHAN KEPERAWATAN KELUARGA PADA KELUARGA TN. M KHUSUSNYA TN. M DENGAN GOUT ARTHRITIS DI RT 05 RW 07 KELURAHAN LIMO KECAMATAN LIMO KOTA DEPOK - Alya Nabila Rojwa (2023)
Gout arthritis, a painful form of arthritis, can develop as a result of repeated bouts of gout pain. In Indonesia, the number of gout sufferers is increasing from year to year, this is due to the adoption of an unhealthy lifestyle, one of which is consuming lots of foods high in purines as well as lack of public knowledge about gout arthritis. The purpose of this research is to report on family nursing care for the TN.M family, especially TN.M with gout arthritis at RT 05 RW 07, Kelurahan Limo, Depok City. The research design of this case uses descriptive research with a case study approach through carrying out nursing assessments, determining diagnoses and scoring, planning nursing actions, carrying out nursing implementation, and evaluating nursing. The results of nursing problems obtained were ineffective family health management related to the inability of families to recognize health problems of family members with gout arthritis health problems, both acute pain related to the inability of families to care for family members, and the third diagnosis, impaired physical mobility related to the inability of families to care for family members with musculoskelatal system problems. It can be concluded that warm compress demonstration activities and range of motion exercises are expected to be included in the nursing action laboratory process. Keywords: Gout Arthritis, Acute Pain, Uric Acid Levels, Ginger Boil Warm Compress